Influence of the idle-up strategy on the thermal management of diesel particulate filter regeneration during a drop to the idle process. (August 2018) - Bai, Shuzhan; Wang, Chunkai; Li, Da; Wang, Guihua; Li, Guoxiang
Graphical abstract: As exhaust temperature and particulate combust speed increased after active regeneration, catalyst carrier temperature increased accordingly; after approximately 80 s, carrier temperature reached steady condition, after approximately 20 s, as particulate consumed, pressure difference of DPF inlet and outlet started to reduce; at this point, diesel engine working condition dropped to idle abruptly, exhaust mass flow reduced from 720 kg/h to 180 kg/h, heat generated from particulate combust could not be taken away in time, carrier temperature raised rapidly. Test results showed center area of the carrier outlet have higher temperature increase; center area of the carrier inlet has lower temperature increase. Therefore, attention of DTI progress shall be concentrate on the temperature of carrier outlet, ensure the peak temperature is sustainable for catalyst and its carrier through thermal management. Highlights: Regenerative temperature field of cordierite ceramic filter was measured. Different idle speeds were tested for DPF regeneration during drop to idle process. Idle-up strategy was provided to decrease the peak temperature and temperature gradient under drop to idle process. Abstract: The idle-up strategy of diesel particulate filter (DPF) regeneration during a drop to the idle (DTI) process was investigated in this study. This strategy could control the peak temperature and maximum temperature gradient of a cordierite ceramic filter. Experimental results showed that as the engine working condition dropped to idle speed during regeneration with a DPF soot load of 4 g/L, the peak temperature was reduced from 820 °C to 632 °C when the idle speed was increased to 1100 r/min, a decrease of 22.9%, while the maximum temperature gradient was reduced from 30 °C/cm to 10 °C/cm, a decrease of 66.7%. The peak temperature and temperature gradient of the DPF cordierite ceramic filterwith DTI during regeneration were effectively reduced. The idle speed range for the idle-up strategy to decrease the peak temperature and temperature gradient of a cordierite ceramic filter was discussed. The maximum idle speed of the idle-up strategy should not be higher than the speed of common engine working conditions in order to avoid DTI during a regeneration increase at current engine driving speed.